Preparation and Evaluation of Polymer Fused Metformin Hydrochloride Sustained Release Tablet - Butola, Mansi; Bhatt, Vikas; Nainwal, Nidhi; Jakhmola, Vikash; Dobhal, Kiran; Ale, Yogita (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Diabetes Mellitus (DM) is one of the most prevalent and chronic illnesses associated with an abnormally high level of glucose in the body which is hazardous to the body organs. Metformin Hydrochloride (HCl), a biguanide derivative is used for Type 2 DM. It has a relatively short plasma half-life and its regular administration is required to maintain a normal blood glucose level in diabetic patients. Therefore, sustained-release medications are a suitable approach to increase patient compliance and extend the duration of the effect of metformin for 8-12 hr. The main goal of this investigation was to prepare an oral sustained-release tablet of metformin HCl using natural polymers as release rate-controlling agents. Materials and Methods: Polymer fused metformin hydrochloride sustained-release tablet was formulated with sodium alginate, and pectin alone and in combinations at different ratios, by direct compression method. Evaluations: The formulation was evaluated for pre-compression parameters, like drug-excipient interaction (using Fourier-transform infrared spectroscopy), drug solubility, flow properties and density of powder blends. The compressed tablets were evaluated for diameter, friability, thickness, weight variation, hardness, content uniformity and in vitro drug release. Results: The drug release study showed that sodium alginate and pectin alone and in combination were able to sustain the drug release. It is also suggested that if the amount of polymer increased, the drug release decreased. Formulation (MA3) containing the highest amount of sodium alginate (250mg) gave 93.06% drug release after 12 hr and was therefore chosen as the best formulation. Diffusion and erosion may be the mechanism of drug release, according to the kinetic modelling of the in vitro drug release.
Keywords: Metformin HCl; Pectin; Sodium Alginate; Diabetes Mellitus